2001
DOI: 10.1095/biolreprod64.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Specific Glycoprotein (PSG) in Baboon (Papio hamadryas): Family Size, Domain Structure, and Prediction of a Functional Region in Primate PSGs1

Abstract: Pregnancy-specific glycoprotein (PSG) constitutes a major component of serum of pregnant women and appears to be essential for a successful pregnancy. Its function is, however, still unknown. Because of the evolutionary divergence between human and rodent PSG, functional studies may require a primate animal model. We have characterized PSG transcripts in a baboon placenta cDNA library and analyzed baboon genomic DNA. The main PSG isoform had the domain structure N-A1-B2-C similar to the human type IIa isoform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…Whilst this finding is consistent with a number of possible integrin-mediated functions, including a disintegrin type function, several studies failed to find an integrin-related mode of action of PSGs (Zhou and Hammarstrom, 2001). However, a recent report of mouse Psg binding to integrin-associated CD9 (Waterhouse et al, 2002), lends further support to the speculation that Psg RGD-like motifs are functional, and suggests that more detailed studies of these motifs are warranted.…”
Section: Discussionsupporting
confidence: 71%
“…Whilst this finding is consistent with a number of possible integrin-mediated functions, including a disintegrin type function, several studies failed to find an integrin-related mode of action of PSGs (Zhou and Hammarstrom, 2001). However, a recent report of mouse Psg binding to integrin-associated CD9 (Waterhouse et al, 2002), lends further support to the speculation that Psg RGD-like motifs are functional, and suggests that more detailed studies of these motifs are warranted.…”
Section: Discussionsupporting
confidence: 71%
“…Snake venoms contain disintegrin proteins that bind integrins and disrupt cell - extracellular matrix interactions or blood clotting mechanisms and, analogously, we and others have hypothesised that PSGs may function as secreted integrin ligands that disrupt integrin function and thereby facilitate invasion of maternal tissues by fetal trophoblast, or disrupt other integrin mediated functions in maternal tissues [6], [24]. We noted that PSG1 has a KGD rather than an RGD motif and, based on the presence of a KGD motif in barbourin, a platelet integrin αIIbβ3 antagonist found in pygmy rattlesnake ( S. m. barbouri ) venom [25], we tested whether PSG1 may be a selective αIIbβ3 ligand.…”
Section: Introductionmentioning
confidence: 95%
“…81 It has been reported that PSG1a can turn macrophages tolerogenic and increase their ability to produce IL-10 and TGFbeta. 82,83 PSGs and particularly PSG-1a can inhibit T-cell proliferation but not directly, they rather do this via macrophages (reviewed in Martinez). Similarly to what is reported for Gal-1 54 and HO-1 27 among others, PSG1a seems to modulate DC phenotype and maturation that finally promotes the secretion of IL-17.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 99%